Development Maternal – Fetal Attachment Promotion Model of Unwanted Pregnant Adolescents Chiang Rai Province - Aryuyuen, Wachiraporn; Chanthamolee , Suree; Suwan, Prapapen; Hoonnirun, Pornsook (Journal of The Royal Thai Army Nurses, 2021)
This research is study and development. with the purpose of: (1) to study the situation of adolescents unwanted pregnancy (2) to develop a model for promoting Maternal-fetal attachment Promotion (3) to evaluate results After the experiment 1 month results the Development of a Maternal-fetal attachment Promotion Model Developed. The study population were adolescents with unwanted pregnancies, In Chiang Rai province, age between 16 - 19 years. The study group was divided into 2 groups, namely (1) the experimental group of 30 people. (2) The control group of 30 people by lottery method. There were 3 sets of qualitative research instruments: 1) in-depth interview, 2) questionnaire, 3) evaluated through content validity check, obtained an CVI value of 0.83 is equal to 0.86 The data was analyzed using descriptive statistics and statistical tests Statistics used Paired t - test The results of the research demonstrated that Pattern development is appropriate in accordance with the behavioral adjustment needs of the pregnant adolescent. Maternal-Fetal Promotion Model applied the created activity plan. Results of comparison before and after the trial Average score. The maternal attachment higher, post-trial, have assessed results the 1-month by the Percentage amount statistically significant of .05